Film and cinephilia in Pakistan : beyond life and death - Ahmed, Nobil Ahmed; Ahmad, Ali Nobil; Khan, Ali, 1969-; Dwyer, Rachel (Karachi : Oxford University Press, 2020)
Film and Cinephilia in Pakistan is a brilliant book of impressive depth and range. Well-written, with a superb introduction, and filled to the brim with theoretical and historical insights, it constitutes a field-defining intervention into Pakistani cinema studies.
Includes bibliographical references (pages 249-261) and index.
Keywords: Motion picture industry -- Pakistan